Hubungan Karakteristik Demografi Dengan Tingkat Kesepian (Loneliness) Pada Lansia Di Wilayah Nusa Tenggara Barat - Sri Yuliana; Khariza Fadhila Syahnaz; Muhd. Firmansyah (NERSMID : Jurnal Keperawatan dan Kebidanan, 2025)
Older adults experience specific problems and limitations, such as cognitive and physical health decline, reduced productive roles, changes in social status, decreased interpersonal support, and loss of health, which may lead to loneliness. This study aimed to examine the relationship between demographic characteristics and the level of loneliness among older adults in West Nusa Tenggara. A cross-sectional study design was employed, and the research was conducted at Posyandu Lansia in Rato Village, Lambu Subdistrict, Bima Region, West Nusa Tenggara, from May to July 2025. 52 respondents participated in this study. The UCLA Loneliness Scale was used to measure the level of loneliness. The results showed that gender (p-value = 0.006) and employment status (p-value = 0.004) were significantly associated with the level of loneliness among older adults. However, no statistically significant association was found between age and educational level with loneliness. Further studies are needed to strengthen these findings. In addition, greater attention from healthcare providers is expected to develop appropriate interventions to reduce loneliness among older adults.